426 A Beat Away from Precision Medicine: Characterizing Human Cardiac Fibroblast Responsiveness to Hemodynamic Unloading in Heart Failure with Reduced Ejection Fraction - Rachel Biggs; Daniel N. Silverman; Yuhua Zhang; Catalin F. Baicu; Michael R. Zile; Amy D. Bradshaw (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Myocardial interstitial fibrosis leads to high hemodynamic load resulting in heart failure (HFrEF). Previous studies show that treatment with a left ventricular assist device (LVAD) does not reduce fibrosis. We hypothesize that human cardiac fibroblasts are highly activated in HFrEF and remain unresponsive to hemodynamic unloading by LVAD. METHODS/STUDY POPULATION: Forty human subjects with HFrEF undergoing LVAD implantation were enrolled to provide a portion of myocardium routinely removed during LVAD placement. In addition, 7 biopsies previously collected from transplanted hearts with extended LVAD treatment were also evaluated (LVEX). RESULTS/ANTICIPATED RESULTS: Quantification of PSR-stained sections reveals a significant increase in collagen content in the HFrEF tissue (CVF = 2.8) compared to control tissues (CVF = 0.9) that remained elevated in LVEX hearts (CVF = 3.1). HCFs from LV biopsies were isolated and grown to confluence. HCFs from HFrEF patients and control HCFs were plated on substrates with stiffnesses reflective of normal myocardium (2kPa) or HFrEF myocardium (8kPa). Cells were collected at 4- and 7-day time points and levels of collagen I and alpha-smooth muscle actin were quantified by western blot analysis. Control HCFs were responsive to changes in substrate stiffness producing more Col I and a-SMA on 8kPa versus 2kPa, HCFs from HFrEF patients were unresponsive to changes in stiffness exhibiting no significant difference in protein production on 2 vs. 8kPa. DISCUSSION/SIGNIFICANCE: Our data suggests that HCFs isolated from the failing myocardium do not respond to changes in mechanical load and might contribute to persistent increases in fibrosis. These findings bring us one step closer to elucidating mechanisms behind fibrosis in HFrEF which could lead to targeted therapies to improve patient outcomes from LVAD support.